What is the hyperbolic function of
(cosh A *cosh B)^2
obviously it is the same thing as cosh^2(A) * cosh^2(B).
Is there any way I could get it to become
cosh^2(A) * cosh^2(B) = Cosh^2(A) + Cosh^2(B) ?
From the cosine law, we can write sin^2(gamma) = 1 - (AB - C / sinh a.sinh b)^2 [where A=cosh a, B= cosh b, C = cosh c]
I have done this. The next part of the question says
deduce
sin^2(gamma) sinh^2(a) sinh^2(b) = 1 - A^2 - B^2 - C^2 +2ABC.
This is where my problem lies, I understand how to get the LHS. I dont see hot to get the RHS
Start using the hyperbolic identities to see what you can do.
Hyperbolic function - Wikipedia, the free encyclopedia